Pengaruh Return on Assets dan Return on Equity Terhadap Harga Saham Pada Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia - Anwar, Rezki Amaliah; Afiah, Nur; Azis, Fajriani (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of return on assets and return on equity on stock prices in property & real estate companies listed on the Indonesia Stock Exchange (IDX). This study is all property & real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 as many as 35 companies. The sampling technique used is the purposive sampling technique. Based on the established criteria, a sample of 11 companies was obtained. Data collection wa carried out using the documentation technique. Data analysis was cerried out using descriptive statistical tests, classical assumption tests, hypothesis tests, and multiple linear tests. The results of the study indicate that: (1) there is a positive and significant influence between Return On Assets (ROA) on Stock Prices, with a statistical t test with a calculated -tvalue greater than the -ttable value, namely (3,197 > 2,019) at a significance of 0,003 < 0,05; (2) there is a positive and significant influence between Return On Equity (ROE) on Stock Prices, with a statistical t test with a calculated -tvalue greater than the -ttable, namely (2,792 > 2,019) at a significant of 0,008 < 0,05; there is a positive and significant influence between Return On Assets (ROA) and Return On Equity (ROE) simultaneously on Stock Prices with a statistical F test with a calculated Fvalue of 14,195 and Ftable 3,22, namely (14,195 > 3,22) at a significance level of 0,000 < 0,05.